Religiousness and Anger toward God: Between Spirituality and Moral Community - Yonathan Aditya; Ihan Martoyo; Jessica Ariela; Rudy Pramono (Religions, 2022)
Religious individuals and communities often struggle with anger toward God (ATG) upon experiencing suffering. ATG is related to poor mental health. Certain types of religiousness can moderate the effect of this negative feeling on well-being; however, research varies. Therefore, this study aims to determine whether religion at the individual (spirituality) or communal levels (moral community) may affect the association of ATG with well-being. Moderation analysis was performed on data from 307 students at a Christian university in Indonesia. Spirituality lowered the effect of ATG as one form of a religious stressor on well-being, but moral community did not. Both the cognitive and affective aspects of spirituality (individual level) are needed to buffer the effects of ATG on well-being. Conversely, the moral/behavior and belonging/communal aspect of a moral community (communal level) do not appear to ensure support for the individual with ATG. The implications of this study are discussed below.